Ensuring auditor independence: The case for small and medium practices in Malaysia - Zainal Abidin, Nor Hafizah; Nelson, Sherliza Puat; Ahmad, Maslina (Asian Journal of Accounting Perspectives, 2021)
Research aim: The study aims to examine small and medium audit firms’ compliance with the independence requirements as stipulated in the International Standard on Quality Control 1 (ISQC 1) in Malaysia. Design/ Methodology/ Approach: This study is qualitative in nature. It uses semi-structured interviews to gather input from 27 managers and partners of small and medium audit firms in Malaysia. Research findings: The findings highlight variations in compliance practices on the independence requirements among small and medium audit firms. Some of the firms partially complied with the independence requirements, whereas others showed non-compliance. The findings further indicate that the majority documented their independence policies and procedures using an audit manual or audit checklist, communicated during the year. The study also found that the lack of financial and physical resources is considered the main hindrance to greater compliance. Theoretical contribution/ Originality: There is a lack of research on the actual compliance with the independence requirements among small and medium firms in emerging economies. This study addressed that gap by focusing on small and medium audit firms in Malaysia. The majority of previous studies on regulatory inspection had focused on Anglo-Saxon countries. Practitioner/ Policy implication: The findings suggest that small and medium audit firms have done their best to comply with the independence requirements despite constraints on financial and human resources. As such, further awareness of the importance of independence would enhance the compliance level as well as audit value and the quality of firms. Research limitation: Interview data were extracted from a small sample; hence, generalisation may need to be defined more cautiously when applied to other contexts. Moreover, since the respondents were selected based on their agreement, the findings reflecting their practices may not be applicable to other small and medium audit firms. Keywords: Independence, Breach and Threat, Small and Medium Firms, Qualitative Research, Interview, ISQC 1 Type of article: Research paper JEL Classification: M42, M480